Analisis Perilaku Cuci Tangan Pakai Sabun Pada Ibu Balita di Puskesmas Pengandonan - Izajah Nopemberia; Lilis Suryani; Maria Ulfa (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2022)
Hand washing with soap (CTPS) is a healthy lifestyle that is easy, inexpensive but clinically effective in preventing the spread of infectious diseases. Children under five have a higher risk of suffering from infectious diseases due to bacterial infections than adults, their immune system is still weak. Therefore, as parents, especially mothers, they are expected to be able to play a role in maintaining the cleanliness of their toddlers, one of them by doing CTPS. Objective: To analyze the behavior of CTPS in mothers of toddlers in the Pengandonan Health Center Work Area. Method: This type of research is quantitative with a cross research design. sectional. The population in this study was the total number of mothers under five living in the working area of ??the Pengandonan Health Center totaling 118 people. The sample was taken using the Slovin formula so that a sample of 91 respondents was obtained using proportional random sampling technique. Data analysis used univariate, bivariate and multivariate. Data collection was done by using questionnaires and interviews. Result : There is a relationship between education level, income, availability of facilities, information exposure and local government support with CTPS behavior with p value = 0.000 or p < 0.05. Conclusion: between education level, income, availability of facilities, information exposure and local government support has a statistically significant relationship with the behavior of CTPS .